SOCIAL ENTREPRENEURSHIP LEARNING BASED ON COMMUNITY EMPOWERMENT OF TOURISM VILLAGE - Muarifuddin,; Kriswanto, Hendra Dedi (PEOPLE: International Journal of Social Sciences, 2020)
This study aims to describe the learning activities of social entrepreneurship and the impact of community empowerment as a manifestation of community empowerment in the management of tourist villages. The approach used is descriptive qualitative. The research subjects were the village head, batik craftsmens, batik makers and several community leaders as informants. Data collection uses interviews, observation and documentation methods. The validity of the data uses sources triangulation, methods, and theories. Data analysis techniques through the stages of data collection, reduction, presentation, and conclusion. The results showed the creation of interactions between craftsmens and batik maker who have established patron-client relationships. Batik craftsmens are involved in business collaboration, realized joint efforts in marketing batik products, which are centered in one batik showroom. The social structure formed shows dependency relations. The impact of community empowerment formed is the creation of an entrepreneurial community and the formation of a batik tourism village center in Babagan village, Lasem sub-district, Rembang district, Central Java province, Indonesia.Learning